1995
DOI: 10.2307/3870162
|View full text |Cite
|
Sign up to set email alerts
|

G Protein Activation Stimulates Phospholipase D Signaling in Plants

Abstract: We provide direct evidence for phospholipase D (PLD) signaling in plants by showing that this enzyme is stimulated by the G protein activators mastoparan, ethanol, and cholera toxin. An in vivo assay for PLD activity in plant cells was developed based on the use of a "reporter alcohol" rather than water as a transphosphatidylation substrate. The product was a phosphatidyl alcohol, which, in contrast to the normal product phosphatidic acid, is a specific measure of PLD activity. When 32P-labeled cells were trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
147
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(152 citation statements)
references
References 0 publications
5
147
0
Order By: Relevance
“…In plants, most reports on PLD functional studies have dealt with its possible effects on membrane deterioration in relation to stress injuries, senescence, aging, and pathogenesis (4 -6). Recent studies have, however, indicated a role of PLD in signal transduction processes in response to environmental cues (7)(8)(9).…”
mentioning
confidence: 99%
“…In plants, most reports on PLD functional studies have dealt with its possible effects on membrane deterioration in relation to stress injuries, senescence, aging, and pathogenesis (4 -6). Recent studies have, however, indicated a role of PLD in signal transduction processes in response to environmental cues (7)(8)(9).…”
mentioning
confidence: 99%
“…PLD in plants was originally proposed to be important in phospholipid catabolism, initiating a lipolytic cascade in membrane deterioration during senescence and stress injuries (1,2). Recent studies in plants, animals, and yeast indicate that PLD hydrolysis plays a pivotal role in transmembrane signaling and cellular regulation (3)(4)(5)(6)(7)(8)(9). Activation of PLD has been proposed to mediate many cellular processes including cell proliferation, membrane trafficking, meiosis, and responses to external and internal stimuli.…”
mentioning
confidence: 99%
“…Most of the studies have involved the use of potential G-protein activators and inhibitors, such as toxins, nonhydrolyzable guanine nucleotide analogues, and alcohols (16,17). In barley aleurone cells, a PLD␣-like activity has been suggested to be associated with a G-protein on the plasma membrane to mediate ABA signaling (17).…”
mentioning
confidence: 99%